ملامح السرد في القصيدة الغزلية عند شعراء الطوائف والمرابطين - محمد، حسن منصور (جامعة ميسان - كلية التربية الأساسية, 2023)
يمثل الغزل أحد أهم الأغراض الشعرية التي حفل بها الشعر العربي، فاهتم به المتلقي اهتماما بالغا؛ لما يحركه فيه من مشاعر وجدانية يلامس بها شغاف القلوب، لذا دأب شعراء الغزل على تخير صورهم الشعرية بما يلائم ويحاكي ذلك الحب والشغف في نفوسهم تارة وفي نفوس متلقيهم تارة أخرى، فنقلوا تجاربهم الغرامية بصور شعرية متعددة الأنواع، فتارة حكوا صبابتهم وما لاقوه من صد الحبيبة أو فراقها، وتارة أخرى وصفوا صفو أيامهم في قرب من أحبوا، وهذا كله لا يأتي مباشرة وإنما اختطوا له طريقا استطاعوا من خلاله تثبيت صورهم الشعرية، وقصائدهم الغزلية حتى جعلوها كالقصة المروية في شخوصها وأحداثها، معتمدين في ذلك ما يعينهم عليه سعة عقولهم، فامتزج بذلك السرد بالشعر؛ كون الأول يمثل الخيمة الكبيرة التي استطاعت أن تغطي أغلب الأنواع الأدبية، فأخذ الشاعر من السرد الوصف والحوار، والمشهدية القصصية التي تعتمد التراتبية في سرد الحدث وتصويره، ونحن هنا لا تحمل القصيدة الغزلية ما لا تتحمله، أو إنا نطلب منها أن تحوي جميع أساليب السرد والقص المعروفة بالقدر الذي نشير فيه إلى قدرة هذه القصيدة على الإفادة من تقنيات السرد وتوظيفها بما يخدم الغرض الذي كتبت فيه الطريقة المتبعة في ذلك، والتمازج بين الشعر والسرد تمازجا قديما، فأرسطو وضع القص ضمن الشعر الملحمي، وبدأ القص في الشعر العربي منذ أن كان الشاعر يركب القفار ويروي رحلته وما يصادفه من أهوال ومتاعب، وما يلقاه في رحلة الصيد والبحث عن الجمان والشهد كما في أشعار هذيل، وعليه فإن الرؤية المعرفية التي ترى فصلا حقيقيا بين الشعر والقص تحتاج إلى إعادة قراءة في منجزها وأحكامها. Love, or ghazal, is one of the most significant poetic genres in Arabic poetry, evoking emotional feelings that touch the depths of the heart and captivating the reader's interest. Ghazal poets are committed to selecting appropriate and meaningful poetic images that reflect the passion and love in their souls and the souls of their audience. Their love experiences are conveyed through a diverse range of poetic images, including expressions of their sorrows and the pain of rejection or separation from their beloved, as well as the description of their happy days in the company of their loved ones. All of this is conveyed through a solidification of poetic images and ghazal poems, making them akin to a narrated story with relatable characters and events. The blending of narrative and poetry is a long-standing tradition, with the former being a big tent that covers most literary genres. The poet draws from the narrative to describe dialogue and story scenes, relying on a hierarchy in narrating events and portraying them. It's important not to burden the ghazal poem with what it cannot bear, or demand that it contains all known narrative and storytelling techniques. Instead, we should appreciate the poem's ability to benefit from and employ narrative techniques to serve its intended purpose, following the method adopted in its creation. The blending of poetry and narrative has a rich history, with Aristotle placing the epic within poetry and storytelling in Arabic poetry beginning with poets narrating their journeys and experiences while hunting for precious things and honey, as seen in the poems of Hatheel. As such, any cognitive vision that separates poetry and narrative requires a re-reading of its achievements and judgments.
Keywords: الأدب العربي -- النقد الأدبي -- شعر الغزل -- السرد القصصي -- شعراء الأندلس